Explicație pas cu pas:
Salutare!
[tex]\bf -3x^{2} \cdot 2x =[/tex]
[tex]\bf -3x^{2} \cdot 2x^{1} =[/tex]
[tex]\bf -6x^{2+1} =[/tex]
[tex]\boxed{\bf -6x^{3}}[/tex]
[tex]\bf (-3x)^{2} \cdot 2x =[/tex]
[tex]\bf 9x^{2} \cdot 2x^{1} =[/tex]
[tex]\bf 18x^{2+1} =[/tex]
[tex]\boxed{\bf 18x^{3}}[/tex]
Regula de semnelor:
Câteva formule pentru puteri:
a⁰ = 1 sau 1 = a⁰
(aⁿ)ᵇ = aⁿ ˣ ᵇ sau aⁿ ˣ ᵇ = (aⁿ) ᵇ
aⁿ · aᵇ = (a · a) ⁿ ⁺ ᵇ sau (a · a) ⁿ ⁺ ᵇ = aⁿ · aᵇ
aⁿ : aᵇ = (a : a) ⁿ ⁻ ᵇ sau (a : a) ⁿ ⁻ ᵇ = aⁿ : aᵇ
aⁿ · bⁿ = (a · b)ⁿ sau (a · b)ⁿ = aⁿ · bⁿ
aⁿ : bⁿ = (a : b)ⁿ sau (a : b)ⁿ = aⁿ : bⁿ
(- a)ⁿ, unde n este o putere impară (-a)ⁿ=(-a)ⁿ
(- a)ⁿ, unde n este o putere pară (-a)ⁿ = aⁿ
#copaceibrainly